Factors influencing the choice of police as prospective career among students of criminology and security studies in Nigeria / Zakariyya Muhammad Sarki dan Mustapha Danjuma Hussein - Muhammad Sarki, Zakariyya; Hussein, Mustapha Danjuma (Universiti Teknologi MARA, 2019)
The aim of this study was to investigate the effect of age, sex, employment status, and CGPA on the choice of joining the Nigerian Police force as a career path among undergraduate students of Criminology and Security Studies bachelor programme of Federal University Dutse, Nigeria. Survey method was used with 80 students selected as sample through proportionate stratified and random sampling. Self-administered questionnaire was used to collect data. It was found that unemployed respondents were most likely to choose police as prospective career due to the hope of contributing towards improving the services of the police organization; female undergraduates were not likely to join the police because of the negative perception or bad image of the organization. Age and sex had no relation with the choice of police as a career among the undergraduate students. It is therefore recommended that graduates of Criminology and Security studies should be considered during police recruitment, and that female students and their family members should be enlightened on the indispensability and importance of having woman in the police service. Furthermore, more efforts need to be put by the police and other relevant agencies to improve the image of the Nigerian police in the eyes of the public.